Clinical utility of liquid biopsy in bladder cancer: The beginning of a new era - Eric Jia; Gautum Agarwal (The Journal of Liquid Biopsy)
Bladder cancer (BC) is the sixth most prevalent cancer in the U.S. and the most expensive to treat. Integrating precision medicine into BC management promises improved outcomes and reduced costs. This review explores current treatment paradigms and the transformative potential of urine-based molecular diagnostics. Treatments for BC range from transurethral resection and intravesical therapy for non-muscle invasive bladder cancer (NMIBC) to neoadjuvant chemotherapy and radical cystectomy for muscle-invasive bladder cancer (MIBC). Recent breakthroughs include enfortumab vedotin with pembrolizumab for advanced urothelial carcinoma, PD-1 immunotherapy for minimal residual disease (MRD)-positive patients and erdafitinib for NMIBC. Traditional diagnostic methods like cystoscopy, urine cytology, and imaging have limitations; urine-based diagnostics, particularly urinary tumor DNA (utDNA) analysis, offer a non-invasive, sensitive, and cost-effective alternative. These diagnostics facilitate personalized treatment, monitor therapy response, detect MRD, and enable earlier cancer detection. Incorporating urine-based diagnostics into clinical practice can reduce healthcare costs and improve patient quality of life. This review highlights the need for these diagnostics in routine BC management and emphasizes the impact of recent therapeutic advances.